A promising technology of cold energy storage using phase change materials to cool tunnels with geothermal hazards. (July 2022) - Zhang, Guozhu; Cao, Ziming; Xiao, Suguang; Guo, Yimu; Li, Chenglin
Abstract: Owing to the limitations, such as low energy efficiency, high cost, and lack of environmental friendliness, of conventional tunnel cooling methods, a novel cold energy storage technology using phase change materials (PCMs) has been proposed to cool tunnels with geothermal hazards. For this technology, geothermal energy from the low ground temperature section is stored in PCM energy storage units using ground heat exchangers (GHEs) to cool the high ground temperature tunnel. A comprehensive literature review was conducted to discuss the feasibility of this technology. The results of the review suggested that: (1) Low ground temperature geothermal energy exists in shallow buried areas at the entrance of high ground temperature tunnels, thus meeting the cooling requirements of high-geothermal environments. (2) Four optional types of GHEs, i.e., horizontal GHEs, vertical GHEs, energy pile GHEs, and tunnel lining GHEs, can be used to extract low ground temperature geothermal energy. Given the heat transfer efficiency, construction convenience, and cost, tunnel lining GHEs may be more suitable for practical applications. The heat exchange rate of tunnel lining GHEs is generally 30–60 W/m 2, and a higher heat exchange rate of 130 W/m 2 can be attained with groundwater flow. (3) To cool high ground temperature tunnels, composite PCMs with melting points of 0–20 °C can be selected to store low ground temperature geothermal energy. PCM plates with heat exchange pipes are recommended for PCM energy storage units. Thus, the proposed novel tunnel cooling technology based on phase change cold energy storage units is feasible. Finally, the possible application of this technology in the Sichuan–Tibet railway of China indicates a bright prospect. Highlights: Conventional cooling methods used in tunnels with geothermal hazards are reviewed. A novel technology of cold energy storage using PCMs for cooling high ground temperature tunnels is proposed. Temperature fields of high and low ground temperature sections inside the tunnel are analyzed. Thermal performances of various types of GHEs are summarized and analyzed. Different PCMs for cold energy storage and PCM energy storage unit are reviewed.